PERLINDUNGAN ANAK DALAM PERSPEKTIF HUKUM ISLAM - Mawardi Sufyan, Akhmad Farid (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2015)
The violence concerning the children can occur everywhere, situation, condition and to all children who unexpectedly before. The closeness of the children such as parents, teachers, and their siblings can be the actor of it. Beginning insulting until employing over the children ability. Who influence psychological and breaking of opportunity to obtain a decent of education and also bounded creativity all of them, this is a figuration about abuse the children that can be done by those who exist around them. The guidance of Islam always put into effect the children was taking care of and save to protection of them, since intrauterine, childhood until they grow up.